2017
DOI: 10.1038/gim.2016.218
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing improves thalassemia carrier screening among premarital adults in a high prevalence population: the Dai nationality, China

Abstract: Methodological comparisons demonstrate the superiority of NGS for both sensitivity and specificity, provide a comprehensive assessment of thalassemia screening strategies, and indicate that NGS is a competitive screening method, especially among populations with a high prevalence of disease.Genet Med advance online publication 26 January 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 31 publications
8
83
0
Order By: Relevance
“…In another study, 49.5% of Dai people were diagnosed as thalassemia carriers via direct NGS screening. By contrast, 22.0% was found by traditional methods in the same cohort. In our study, we identified 40 genomic variations including 11 rare and novel mutations by combined NGS and Gap‐PCR.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In another study, 49.5% of Dai people were diagnosed as thalassemia carriers via direct NGS screening. By contrast, 22.0% was found by traditional methods in the same cohort. In our study, we identified 40 genomic variations including 11 rare and novel mutations by combined NGS and Gap‐PCR.…”
Section: Discussionmentioning
confidence: 64%
“…With the advent of NGS techniques in recent years, NGS emerged as a popular tool in prenatal screening . So far, many recent investigations confirmed the advantage of NGS in screening thalassemia carriers and detecting novel and complex variations . An investigation of prevalence and genetic background of thalassemia in Baise Region found 24 common variations and 4 rare novel variations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a strategy of carrier screening by simply sequencing the whole alpha and beta globin gene clusters by next generation sequencing without any haematological screening has already been shown to be possible in a high-prevalence Chinese population. The authors claimed that NGS sequencing on its own was an improvement over haematological screening, no carriers were missed and some carriers were identified for which haematological screening would have diagnosed as normal [10]. However it was concluded that knowledge of haematological screening data and Hb pattern analysis data was still required in order to understand the importance of some of the globin gene DNA sequence changes revealed by the next generation sequencing data and thus the best carrier screening practice in the future will still require a combination of a patient's haematological data and Hb pattern analysis and a knowledge of thalassaemia and Hb variant genotype-phenotype relationships in addition to the patient's genomic sequence data.…”
Section: Discussionmentioning
confidence: 99%